Techniques of generalisation in computer-assisted cartography in the realm of artificial intelligence - Yusuf, Matharuddin (Fakulti Ukur dan Harta Tanah, 1994)
Generalisation has been a major component of the cartographic method. The principles and practices of generalisation of cartographic elements in an automated system should not be assumed to be the same as those in manual cartography. In this paper an appraisal of the techniques and problems of generalisation, especially relating to those presented by computer technology, are advanced together with some reference to artificial intelligence and requirements of future tools for the provision of solutions to the problems.